When is a Current Account Deficit Bad? - Devadas, Sharmila; Loayza, Norman (World Bank, Washington, DC, 2018)
A current account deficit is sustainable when its underlying drivers support a smooth correction in the future. It is unsustainable when symptomatic of macroeconomic imbalances that would eventually trigger disruptive adjustments. Although a current account deficit in itself is neither good nor bad, it is likely to be unsustainable and lead to harmful consequences when it is persistently large, fuels consumption rather than investment, occurs alongside excessive domestic credit growth, follows an overvalued exchange rate, or accompanies unrestrained fiscal deficits. Even though a current account deficit is often paralleled by deteriorating net foreign assets, it may not be as informative about immediate-term financial vulnerabilities as the size, maturity, and currency composition of gross financial stocks.